ANTHOCYANIN PROFILE AND ITS ANTIOXIDANT ACTIVITY OF WIDELY USED FRUITS, VEGETABLES, AND FLOWERS IN THAILAND - Chaiyasut, Chaiyavat; Sivamaruthi, Bhagavathi Sundaram; Pengkumsri, Noppawat; Sirilun, Sasithorn; Peerajan, Sartjin; Chaiyasut, Khontaros; Kesika, Periyanaina (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Anthocyanins are the water-soluble pigments most commonly present in flowers, fruits, and vegetables. Anthocyanins have been reported for is antioxidant, anti-inflammatory, antibacterial properties and other health benefits in human. This study was performed to extract and determine the anthocyanin and to access the antioxidant properties of the most commonly used fruits, vegetables and flowers in Thailand. Methods: Extraction of anthocyanin and its aglycones from the selected samples and determination of anthocyanin and anthocyanidins using reversed-phase HPLC analysis. Determination of total antioxidant ability using ABTS, DPPH and FRAP assay. Results: Maximum distribution of tested anthocyanin and anthocyanidin contents was observed in the extracts of Jambolan plum, Ceylon Spinach, Purple Sweet Potato, Purple Lettuce followed by common plum and Red dragon fruit. The extracts of Ma-Kiang, Purple Eggplant, Red Grape, and Purple Lettuce showed the maximum amount of cyanidin 3-glucoside, delphinidin 3-glucoside, peonidin 3-glucoside, and malvidin 3-glucoside, respectively. Likewise, the maximum concentration of cyanidin, delphinidin, peonidin, and malvidin were found in Common plum, Red Khae, Red Cabbage, and Purple Lettuce, respectively. Ma-Kiang extract exhibited the maximum antioxidant activity followed by Red Cabbage, Common Plum, and Purple Eggplant extract compared to the other extracts. Conclusion: The present study, primarily profiled the anthocyanin content of selected fruits, vegetables, and flowers. Among the tested samples, Ma-Kiang extract showed the high cyanidin 3-glucoside content and antioxidant activity. Further, detailed study on the content of anthocyanins at different climate and geographical conditions and other factors are necessary to develop nutraceutical or cosmetic product with a functional ingredient. Keywords: Anthocyanin, Anthocyanidin, Antioxidant activity.